The Gulf states and the Horn of Africa : interests, influences and instability - Mason, Robert, 1979-; Mabon, Simon (Identities and geopolitics in the Middle East., 2022)
"The Gulf States and the Horn of Africa takes a deep dive into the complexities of power projection, political rivalry and conflict across the Red Sea and beyond. Focusing on the nature of interregional connections between the Gulf and the Horn, it explores the multifaceted nature of relations between states and the two increasingly important subregions. Bringing together scholars working on and in both regions, the book considers strategic competition between Saudi Arabia and Iran, and between the UAE and both Qatar and Turkey, along with other international engagement such as joint anti-piracy operations, counterterrorism cooperation, security assistance, base agreements and economic development. Drawing on a range of subject expertise and field research across case study countries, the volume adds to the sparse literature on the regional and international politics of the Horn of Africa and Red Sea, gleaning specific insights from contemporary reflections across the book. This is essential reading for students and researchers interested in the Horn of Africa and the evolving regional geopolitics of the Gulf."--